The use of momentum, contrarian and buy-&-hold strategies: survey evidence from fund managers - Ulrich Schmidt; Lukas Menkhoff; Torsten Brozynski (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2003)
This study provides evidence from a questionnaire survey of fund managers. We find that the majority of respondents rely on momentum, contrarian and buy-&-hold strategies to some degree. Although there were few applicants who exclusively rely on a single trading strategy, clear preferences emerged. All kinds of predetermined trading strategies are preferred by younger and less experienced professionals. Moreover, contrarian traders show signs of overconfidence, disposition effect and reliance on non-fundamental information. A more conventional contrast is provided by fundamentally oriented and risk averse buy-&-hold traders, whereas momentum traders appear as the least risk averse professionals who may aim for exploiting the sub-optimal behavior of others. – – Die vorliegende Studie basiert auf Erkenntnissen einer schriftlichen Befragung von Fondsmanagern. Es zeigt sich, dass die Mehrzahl der Befragten Momentum, Contrarian sowie Buy-&-Hold Strategien verfolgen. Obwohl sich wenige exklusiv auf eine bestimmte Strategie verlassen, zeigen sich klare Präferenzen. Die Gesamtheit der genannten Handelsstrategien wird von jüngeren und weniger erfahrenen Professionals bevorzugt. Ferner neigen Contrarian Manager zur Selbstüberschätzung, unterliegen tendenziell einem Dispositionseffekt und stützen ihre Investmententscheidungen vorrangig auf nichtfundamentalen Informationen. Einen Kontrast liefern fundamental-orientierte, risikoaverse Buy-&-Hold Manager, während Momentum Manager die geringste Risikoaversion aufweisen und möglicherweise darauf abzielen, das suboptimale Verhalten der anderen auszunutzen.
Keywords: G23; G14; 330; momentum trading; buy-&-hold strategy; contrarian strategy; market efficiency; Wertpapierhandel; Strategie; Anlageverhalten; Investmentfonds; Deutschland